Sub-terahertz testing of millimeter wave Monolithic and very large scale integrated circuits. (May 2019) - Shur, M.; Rudin, S.; Rupper, G.; Reed, M.; Suarez, J.
Highlights: THz testing of MMICs and VLSI circuits could be done by measuring the response at the pins. This technique could be used to evaluate the reliability and lifetime of integrated circuits. It was demonstrated using a working and damaged MMIC with just a few transistor. This technique can use machine learning for establishing the evolving database of the responses. Abstract: Comprehensive Testing of Microwave Monolithic Integrated Circuits (MMICs) and Very Large Scale Integrated (VLSI) circuits is a problem of growing sophistication and importance. A commensurate problem involves the increasing relevance of hardware security, with rapidly increasing dependence of U.S. industry on imported electronics. Non-destructive, unobtrusive testing techniques are especially useful but hard to implement. In this paper, we report on using THz scanning of MMICs and VLSI circuits for testing, identification, and validation by measuring the circuit response at the pins. This technique could also be used to evaluate the reliability and lifetime of integrated circuits. This technique was demonstrated using a working and damaged MMIC with just a few transistors. For larger-scale circuits, this technique can be combined with machine learning for establishing the evolving database of the responses processed by an artificial-intelligence algorithm.